An Eulerian model for forest residues gasification in a plasma gasifier. (1st September 2019) - Ismail, Tamer M.; Monteiro, Eliseu; Ramos, Ana; El-Salam, M. Abd; Rouboa, Abel
Abstract: A new mathematical model for plasma gasification was adopted and added to the COMMENT homemade code. The COMMENT code is dedicated to coupled transfer applications in the fields of thermal, fluid mechanics and chemical engineering, both solid and gaseous states being assessed. Phenomena like continuity, species transport, heat transfer, turbulence and chemical reactions were taken into account. Plasma gasification of forest residues was simulated within defined conditions and assumptions, the producer gas being monitored and characterized. The presented model was validated against literature data. A high level of agreement between the numerical and the experimental values was achieved, proving that the model is robust and suitable for the proposed goal. This new model requires low computational capacity and allows a wide range of reactor types to be used in the gasification process. A parametric study was also conducted in order to understand the influence of some variables on gasification products and their concentrations along the runs. It was possible to conclude that lower equivalence ratios (ER) favored H2 and CO production as well as lower heating value (LHV), while higher ER values enhanced N2 contents, carbon conversion efficiency (CCE) and minor alterations were observed for CH4 and CO2 . H2, N2 and CO2 as well as CCE and cold-gas efficiency (CGE) were also enhanced by higher steam-to-biomass ratios (SBR), while CO content and LHV dropped, CH4 remaining almost unaltered. For higher temperatures H2, CO and N2 levels were improved as well as LHV, whereas CO2 and CGE were reduced and CH4 remained unchanged. The results showed that the model proposed in this study is a promising tool for simulating the plasma gasification process of biomass within a gasifier. Highlights: Biomass plasma gasification process was performed using Eulerian model. Different biomasses were evaluated in order to assess SYNGAS relative production. Lower equivalence ratios (ER) favored H2 and CO production as well as LHV. Higher ER enhanced N2 yields and CCE, minor changes being seen for CO2 and CGE. For higher temperatures H2, CO and LHV were improved, CO2 and CGE were reduced.